2021
DOI: 10.1136/neurintsurg-2020-016994
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of thromboembolic complications during the endovascular treatment of unruptured aneurysms by employing a tailored dual antiplatelet regimen using aspirin and prasugrel

Abstract: BackgroundThromboembolic complications (TECs) are frequent during the endovascular treatment of unruptured aneurysms. To prevent TECs, dual antiplatelet therapy using aspirin and clopidogrel is recommended for the perioperative period. In patients with a poor response, clopidogrel is a risk factor for TECs. To prevent TECs, our study assessed the stratified use of prasugrel.MethodsPatients who underwent endovascular therapy for unruptured cerebral aneurysms from April 2017 to August 2019 were enrolled in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…Still, some individuals show genetic variation, failing to respond to CPG [ 12 15 ], and there is no consensus regarding the exact types and doses of antiplatelet therapy. PSG has been reported to be effective for patients with inadequate response to CPG [ 6 ]. In this study, all patients received PSG and the PRU was significantly decreased after changing CPG to PSG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, some individuals show genetic variation, failing to respond to CPG [ 12 15 ], and there is no consensus regarding the exact types and doses of antiplatelet therapy. PSG has been reported to be effective for patients with inadequate response to CPG [ 6 ]. In this study, all patients received PSG and the PRU was significantly decreased after changing CPG to PSG.…”
Section: Discussionmentioning
confidence: 99%
“…Before the procedure, all patients received dual antiplatelet therapy with clopidogrel (CPG) at 75 mg and aspirin at 100 mg for 14 days. P2Y12 reaction unit (PRU) was monitored by VerifyNow (Accumetrics, San Diego, CA, USA) 2 days before the procedure, and CPG was changed to prasugrel (PSG) in all patients [ 6 ]. In patients whose PRU was greater than 210, a loading dose of PSG at 20 mg was administered; subsequently, a dose of PSG at 3.75 mg per day was maintained.…”
Section: Methodsmentioning
confidence: 99%
“…Neurointerventional studies, however, have used different cutoffs in varied contexts, varying from 208 to 295. 12,20,[27][28][29]31,40,54 A value of ,60 was reported to be associated with a higher risk of hemorrhagic complications. 28,29 In a study of 279 patients under dual antiplatelet therapy, a value of 175 was observed to discriminate patients with hemorrhagic complications from those without.…”
Section: Clopidogrel Resistance In Interventional Neuroradiologymentioning
confidence: 99%
“…In a recent study, Higashiguchi et al, 31 in 2021, proposed a tailored therapy in which prasugrel replaced clopidogrel when the result of the VerifyNow assay was inferior to 240 P2Y12 reactive units. They observed a reduction in the frequency of thromboembolic complications after treatment of unruptured aneurysms (16% versus 6%, P , .048, n = 217) after a 1-month follow-up without an increase in the rate of hemorrhagic complications.…”
Section: Clopidogrel Resistance In Interventional Neuroradiologymentioning
confidence: 99%
See 1 more Smart Citation